Prevalence of falls and associated factors in community-dwelling older Brazilians: a systematic review and meta-analysis - José Elias Filho; Wyngrid Porfirio Borel; Juliano Bergamaschine Mata Diz; Alexandre Wesley Carvalho Barbosa; Raquel Rodrigues Britto; Diogo Carvalho Felício
Falls determine huge epidemiological, clinical, and economic burden in the older population worldwide, presenting high odds of severe disability. The present study aimed to estimate the prevalence of falls and associated factors in older Brazilians using a systematic review with meta-analysis. Searches were performed in SciELO, PubMed, LILACS, Web of Science, Scopus and PsycINFO databases with no date or language restrictions. Studies on community-dwelling older persons aged ≥ 60 years from both sexes and with a sample size of ≥ 300 participants included. Exclusion criteria were studies conducted specifically for older adults diagnosed with chronic disabling diseases that predispose them to falls. Risk of bias of included studies was assessed using a critical appraisal tool focusing on prevalence designs. A random-effects meta-analysis was used to pool the prevalence of falls across studies. Exploratory analysis was conducted examining subgroup estimates, prevalence ratios and meta-regression. Thirty-seven studies involving 58,597 participants were included. Twelve-month prevalence of falls was 27% (95%CI: 24.3-30.0), with significantly higher estimates in female than male (PR = 1.57; 95%CI: 1.32-1.86), in age group ≥ 80 years than age group 60-69 years (PR = 1.46; 95%CI: 1.15-1.84), and in participants from the Central region than participants from the South region (PR = 1.36; 95%CI: 1.10-1.69) of Brazil. Risk of bias scores did not impact heterogeneity in the 12-month meta-analysis. These estimates strongly support evidence-based public interventions to prevent falls in older Brazilians, especially in women and the oldest-old population.